Socioeconomic importance of livestock reared in backyard in rural localities of Yucatan and Campeche - Magaña Magaña, Miguel Ángel; Valdivieso Pérez, Ingrid Abril; Aguilar Urquizo, Edgar (Acta Universitaria, 2022)
This research was carried out in rural Mayan localities of the Yucatan Peninsula, Mexico. The objective was to evaluate the contribution of backyard livestock production to family economy. The information was obtained through interviews carried out with mothers head of households through statistical sampling by conglomerates and census. The data collected was analyzed using descriptive statistics and Pearson's correlation. The results indicate that, in their backyard, families prefer to raise animals that they can include in their diet, such as poultry and pigs; however, its production level does not satisfy family demand because most of it is destined for sale. It is concluded that the rearing of animals in backyards provides quality animal protein as well as an immediate income, additional to that of agricultural activities and salaried jobs of family members.